UNIQUE THREATS EXISTING IN CYBER SPACE (Scientific journal of the Fergana State University, 2023)
This article describes the theoretical and methodological foundations of the concept of cyberspace. Existing threats in cyberspace are comparatively analyzed and the theoretical and practical work done on the problem of cyber threats in the international arena is studied.